(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
The future direction of Internet banking focuses on mobile banking which enables client-based banking applications on mobile devices. This shift will enhance productivity, reduce cost, increase profit, and enables customization. The main aim of this research is to develop a demographical adoption model based on the Technology Acceptance Model (TAM) and Information Systems Success (IS SUCCESS) model. The demographic factors and IS SUCCESS Factors are investigated to assess their influence on intention to use of mobile banking applications via descriptive and inferential statistical analysis. The total sample comprising of 395 respondents from Jordanian bank clients in bank branch offices within five major cities in Jordan is used for analysis. Results of the analysis revealed evidence that the young generation with high level of education and income are the most adopters of mobile banking application. The findings of this research are expected to lead to an understanding of how demographic factors and IS SUCCESS Factors the adoption of mobile banking applications in developing countries, which will in turn play an important role in increasing the level of adoption of mobile banking in such countries.